THE PROBLEM OF TRAINING OF LEADERSHIP COMPETENCIES AND ITS SOLVING STRATEGIES AT THE CONTEMPORARY HIGH SCHOOL - Skarbaliene, Aelita (European Scientific Journal, ESJ, 2013)
N.Gehrke as far back as in 1991 proposed that in pursuance of more teachers to take the role of leaders the systematic attitude to this question is necessary and provided arguments that it is needed to begin preparing students for the leadership at high school. These and other similar arguments encouraged to look at training of the leadership competencies at the high school with greater attention. Therefore, in this leadership publication the role of high schools in the process of training of the leadership competencies is reasoned, the problem of training of the leadership competencies at high school is revealed as well as the main strategies of training of the leadership competencies at high schools are surveyed.